Utilization of E-learning in The Learning Process - Alfiyandri, Alfiyandri; Inra, Azwar; Edidas, Edidas (Universitas Pendidikan Ganesha, 2020)
The problem in this research is that e-learning has not been fully implemented by all lecturers of FT UNP, the low participation of lecturers in uploading lecture material using e-learning at FT UNP, the low participation of students in downloading lecture material using e-learning at FT UNP, there is a gap in take advantage of e-learning between students and other students at FT UNP and there has never been an evaluation of the implementation of e-learning at FT UNP. The purpose of this research is to explain the implementation of e-learning in terms of context, input, process and product components. The results obtained from this study can be concluded that the context, input, process, and results component on the implementation of e-learning in the Faculty of Engineering, Padang State University are in good category. Process and outcome components need to be improved, so that the implementation of e-learning can be carried out optimally. Based on the findings of this study, it can be recommended that the implementation of e-learning can be continued by making improvements to each of its components.